Indole 3-acetate and response to therapy in borderline resectable or locally advanced pancreatic cancer - Peder R. Braadland; Peder R. Braadland; Ingvild Farnes; Ingvild Farnes; Elin H. Kure; Elin H. Kure; Sheraz Yaqub; Sheraz Yaqub; Adrian McCann; Per M. Ueland; Per M. Ueland; Knut Jørgen Labori; et al. (Frontiers in Oncology)
Background/AimsIt was recently reported that a higher concentration of the bacterially produced metabolite indole 3-acetate (3-IAA) in blood was linked to a better response to chemotherapy in patients with metastatic pancreatic ductal adenocarcinoma (PDAC). Here, we aimed to extend these observations to patients diagnosed with non-metastatic PDAC.MethodWe measured circulating 3-IAA in samples from a prospective population-based cohort of 124 patients with borderline resectable or locally advanced PDAC, collected before initiating neoadjuvant chemotherapy. The majority (61%) of the patients were treated with FOLFIRINOX. We used univariable and multivariable Cox proportional hazards regression to estimate the association between pre-treatment 3-IAA and overall survival.ResultsThe median serum 3-IAA concentration before chemotherapy was 290 (interquartile range 203–417) ng/mL. The unadjusted hazard ratio (HR) for pre-treatment log2(3-IAA) was 0.93, 95% confidence interval (CI) [0.74–1.16], p=0.52. When adjusting for age, ECOG, CA19-9 and tumor classification, the HR for log2(3-IAA) was 0.87, 95% CI [0.68–1.12], p=0.28.ConclusionOur findings suggest that the potentiating effect of 3-IAA observed in metastatic PDAC undergoing chemotherapy may not translate to borderline resectable or locally advanced PDAC. We recommend additional clinical validation of 3-IAA’s predictive value in different categories of PDAC before implementation attempts in human studies are initiated.